RANCANG BANGUN SISTEM REKOMENDASI PENERIMAAN BARISTA DENGAN MENGGUNAKAN METODE AHP DAN TOPSIS - Aditya Nugraha, - (2020)
Along with the proliferation of businesses in the coffee sector in Indonesia, especially in the city of Bandung, making a barista become a struggle for business people in this coffee business. Certainly not a very easy thing to choose a barista that is also in accordance with the wishes, because there are several factors used in the selection of baristas, including managing raw materials, managing equipment and supplies, managing work areas, Handling Customers, operate equipment, develop coffee products, Handle conflict situations, and Communicate English. One way to simplify these problems is to utilize information technology in processing barista data processing. One technological advance that can overcome this is the existence of a barista acceptance recommendation system using the Analitical Hierarchy Process (AHP) method, Technique for Order Performance of Similarity to Ideal Solution (TOPSIS). The AHP method does the weighting of criteria to produce a value for each criterion, where the results of each criterion are used to get a ranking of alternatives with TOPSIS. Combining these methods can optimize the weighting of criteria values that affect the ranking results of more objective alternatives.